Problema do caixeiro-viajante aplicado à distribuição de vacinas contra COVID-19: - Aguiar, Milas Eduardo Brito de (Universidade Federal do Tocantins, 2023)
The purpose of this article is to study a model of physical distribution of vaccines in the city of Araguaína, Tocantins. In this system, the origin of the loads is a Municipal Immunization Center (MIC), and the destinations are the Basic Health Units (BHU) of the city. The objective of this study is to optimize the routes of the process of delivery of vaccines against Covid-19 in the city using an Operational Research (OR). This work is justified by the importance of availability of availability for the general population. For this, several platforms were used to collect geographic data from each BHU, the distance between each pair of points to be served, the demand in all health units and the capacity of the vehicle responsible for transporting immunobiologicals. Using mathematical models, it was possible to generate optimal solutions for the problem. The solution obtained is a distribution system with multiple traveling salesmen, that is, more than one route for proper service at all points of demand.